Rates and Risk Factors for Revision Hip Arthroscopy - West, Christopher R (Iowa Orthop J, 2019)
BACKGROUND: Revision hip arthroscopy often serves as a measure for a failed primary hip arthroscopy procedure. The purpose of this study was to examine the rate, timing, and risk factors for revision hip arthroscopy using a large national database. METHODS: The Humana administrative claims dataset was reviewed from 2007 through the second quarter of 2015 to identify patients undergoing hip arthroscopy using Current Procedural Terminology (CPT) codes and laterality modifiers. Patients with subsequent ipsilateral revision hip arthroscopy were identified and the rate and timing of these revisions determined. Subgroup analysis was performed to determine effects of gender, age, body mass index (BMI), osteoarthritis diagnosis, and specific hip arthroscopy procedure on revision rates. RESULTS: There were 1807 hip arthroscopy procedures identified with a revision rate of 4% (total of 72 procedures). Of the revision procedures, 43% occurred within 6 months after the index procedure, and 86% occurred within 18 months. Age < 50 years was the only significant predictor of revision hip arthroscopy (OR 2.03, CI 1.173.53) with an even distribution across younger age groups. An osteoarthritis diagnosis, gender, and BMI did not represent significant risk factors for revision (OR 0.87, 0.98, 0.9 and CI 0.5-1.51, CI 0.6-1.59, CI 0.37-2.12, respectively). Chondroplasty was the most common procedure leading to revision (46%) followed by labral repair (37%). The most common revision procedures were chondroplasty (44%) followed by femoroplasty (38%). CONCLUSIONS: Overall, 4% of hip arthroscopy procedures underwent revision arthroscopy over the 8-year period. Revision was associated with age < 50, and revisions were most frequently performed for femoroacetabular impingement. The majority of revisions occurred within 18 months after the index procedure. Level of Evidence: IV